Optimization of Regional Revenues Through Tax Revenues Regulation - Mirza Nasution; Muhammad Yusrizal Adi Syaputra (Universitas Negeri Gorontalo, 2022)
This study aims to examine the Role and Function of the Agency for tax management and regional levy of North Sumatra Province in improving regional income. The research method used is normative legal research method with secondary data. Qualitative analysis is used to analyze problems. The results of the research obtained that Local Tax and Levy Management Agency plays an important role in the improvement of Locally-Generated Revenue North Sumatra through the receipt of Local Taxes. Regional Tax Receipts derived from Motor Vehicle Tax and Public Surface Water in North Sumatra are still low because that Local Tax And Levy Management Agency North Sumatra has not had a strategic policy that can support and improve the Locally-Generated Revenue of North Sumatra Province through Motor Vehicle Tax and Public Surface Water, a Limited number of human resources and low quality of human resources competencies in Local Tax And Levy Management Agency North Sumatra is one of the obstacle factors that Local Tax and Levy Management Agency does not run optimally.